PERUBAHAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI MELALUI THERAPEUTICAL GARDENING DI UPT PSLU MAGETAN - Ayu Permata Sari; Ah. Yusuf; Erna Dwi Wahyuni (Universitas Airlangga, 2019)
Introduction: Aging process affects physical and mental changes that lead to lower resistance, resulting in the onset of various diseases and most commonly found is hypertension. Therapeutic gardening is hobby that can be used as a medical therapy to lower blood pressure. The purpose of this study was to determine the effectiveness of therapeutical gardening in blood pressure changes in elderly with hypertension in UPT PSLU Magetan.Methods: This study was a pre-experimental study using one-group pre-post test design. The population was elderly with hypertension at UPT PSLU Magetan. Sampling technique used was purposive sampling with 10 respondents who were selected based on inclusion criteria. The independent variables in this study was therapeutical gardening and the dependent variable was blood pressures, which were measured with sphygnomanometer and stethoscope. Data were analyzed using paired t test with significance value p < 0.05.Result: The average of systolic blood pressure pre-test was 161 mmHg and post-test was 149 mmHg with paired t test showed p = 0.013 and the average of diastolic blood pressure showed pre-test was 83 mmHg and post-test was 79 mmHg and paired t test showed p = 0.037, that showed therapeutical gardening is effective to change blood pressure in elderly with hypertension.Discussion: Therapeutic gardening effectively changes blood pressure in elderly withhypertension, so that the elderly are expected to perform therapeutical gardening as one of nonpharmacological alternative to lowering blood pressure, because it can be done independently or together and does not cause side effects.